German Economy Autumn 2023: German Economy gradually overcomes stagnation - Jens Boysen-Hogrefe; Dominik Groll; Timo Hoffmann; Nils Jannsen; Stefan Kooths; Nils Sonnenberg; Vincent Stamer (Kiel Institute for the World Economy (IfW Kiel), 2023)
The outlook for the German economy has deteriorated over the last month. Although, the high level of sick leave and supply bottlenecks have noticeably eased, GDP has not yet returned to an expansionary course. Business surveys indicate that economic momentum will remain weak in the second half of the year. Overall, GDP is expected to decline by 0.5 percent in the current year (summer forecast: -0.3 percent). In 2024, economic activity is expected to pick up again. The strong real wage increases will stimulate activity in the consumer-related industries. Given the high order backlogs, the manufacturing industry will also be able to ramp up its production somewhat, even if no major impulses are expected from the global economy for the time being. In contrast, the slump in the construction industry will have a negative impact. Overall, we expect GDP to increase by 1.3 percent (summer forecast: 1.8 percent). For 2025, we expect a growth rate of 1.5 percent. Towards the end of the forecast period, however, the growth rates will approach the low levels that the German economy is likely to face in the medium term. Inflation will fall significantly because the general upward trend in prices will weaken and energy prices will fall at least somewhat. After 6 percent this year, inflation will probably be around 2 percent in the next two years. The current phase of economic weakness will have only a small effect on the labour market, as the shortage of skilled workers remains high. Due to demographic change, employment is expected to stagnate over the next two years. Despite the economic recovery, the government's budget deficit is likely to decline only slightly - from 2.6 percent relative to GDP in the current year to 1.9 percent in 2025. The debt level will be around 64 relative to GDP in the forecast period.
Keywords: 330